Dinamika Penjualan Offline Di Tengah Perkembangan Platform E-Commerce: Studi Kasus Pada Diva Swalayan - Junaedi, Deddy; Putri, Dita Utari Yulia; Taggyah, Istiana Kudsi Falqi; Widiyanto, Karin Syafira; Zuhri, Nadia Muthiah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The rapid growth of e-commerce has presented significant challenges to the sustainability of traditional retail businesses, including local supermarkets. This study aims to analyze the dynamics of offline sales at Diva Swalayan amidst the digital disruption caused by e-commerce platforms. In this study, a descriptive qualitative approach with a case study method is applied, using observation, in-depth interviews, and document collection techniques. The results showed that despite a decrease in the number of visitors due to the increasing interest in online shopping, Diva Swalayan still managed to maintain its business operations through adaptive strategies. These strategies include fast service, personal interaction with customers, promotions through the WhatsApp application, and low-cost delivery services. Elements such as trust, emotional closeness, and convenience in direct shopping are key determinants in maintaining customer loyalty. The conclusion of this study confirms that local retailers can survive in the digital era with a hybrid strategy that combines the strengths of traditional services and a simple digital approach.